Geschichte des hethitischen Reiches - Klengel, Horst. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
The Anatolian people of the Hittites (ca. 1700-1200 B.C.) are the subject of the underlying work. In recent decades scholars have increased our knowledge in the field enormously without bringing the new insights together in a new comprehensive handbook. This long-awaited handbook deals with the whole of the influential political history of the Hittite Empire. After an introduction on the natural conditions of Anatolia, chapters follow on the Hittite history of the early period, the old kingdom of the Hittites, the 'middle' kingdom and, extensively, the new kingdom or empire period. The book is organized chronologically, and each chapter starts with a section on the sources and secondary literature, followed by the actual text on the subsequent periods. In a separate chapter Professor Fiorella Imparati offers a survey on the political structure of the Hittite Kingdom and its foreign policy. Chronological tables, a bibliography arranged by the subsequent periods, a section on problems, and several illustrations conclude this important volume. Given the tremendous amount of material and its lucid organisation this will be one of the few reference works on the Hittites for years to come.